Seeking help from close, same-sex friends: Relational costs for Japanese and personal costs for European Canadians. (June 2015) - Ito, Kenichi; Masuda, Takahiko; Komiya, Asuka; Hioki, Koichi
Seeking help from close friends is beneficial for help seekers but also entails costs. Past research on social support suggested that East Asians were more likely than their North American counterparts to perceive relational costs (e.g., causing trouble for close friends), whereas North Americans tended to selectively perceive personal costs (e.g., admitting incompetence). We first collected European Canadian and Japanese people's everyday experiences of help-seeking behaviors. We then examined whether norms would mediate the relationship between perceptions of costs and expected closeness in friendship. For European Canadians, we found such meditating relationships only for personal costs; whereas for the Japanese, the relationships were observed for both personal and relational costs. Implications for social cognitive research and clinical research are discussed.